Legal Protection Regarding Medical Record of Prospective Workers in Job Recruitment Health Test - Jafar, Faisal Herisetiawan (Law Research Review Quarterly, 2020)
Health is essentially one of the supports for the welfare of human life, therefore, in order to create an increase in the degree of health, a law is needed to regulate and foster everything about health. In the process of getting a decent job several agencies or companies apply a health test at the stage of completion of work acceptance. Health checks before work are health checks carried out by doctors before a worker is accepted to do the jobs. Problems arise when the results of a medikal examination or medikal record in the form of a file containing records and documents about the patient's identity, examination, treatment, actions and other services that have been provided to patients out are fully provided to the agency or employer. This type of research is a normative legal research method. Normative legal research means that the existing problems are examined based on existing laws and regulations and the literature relating to the existing problems. Based on the results of the study that the authors describe, it can be concluded that in the implementation of health tests carried out by the agency or company are not allowed to take the results of the medikal record unilaterally without giving access to prospective workers as parties who are the object of examination at the health test.